2023
DOI: 10.7759/cureus.44687
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nursing Care in Monkeypox (Mpox) Patients: Differential Diagnoses, Prevention Measures, and Therapeutic Interventions

Tanishq Dubey,
Swarupa Chakole,
Suyash Agrawal
et al.

Abstract: Monkeypox (Mpox), a rare zoonotic viral infection caused by the monkeypox virus, has been gaining attention due to its potential for human-to-human transmission and its clinical resemblance to other poxvirus infections, such as smallpox and chickenpox. Enhancing nursing care for monkeypox patients is imperative to manage and contain its spread effectively. This review analyzes the key aspects of enhancing nursing care in monkeypox patients, focusing on differential diagnoses, prevention measures, and therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Nurses’ mental health is an important aspect that interferes with their ability to work. Counseling is considered an effective strategy to enhance mental health and reduce psychological problems, including stress ( Ahmed, M-Amin, et al, 2022 ; Dubey et al, 2023 ; Hans et al, 2022 ; Ibrahim et al, 2022 ; Nimbi et al, 2023 ). It is regarded as a part of regular follow-up by psychologists during this pandemic of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses’ mental health is an important aspect that interferes with their ability to work. Counseling is considered an effective strategy to enhance mental health and reduce psychological problems, including stress ( Ahmed, M-Amin, et al, 2022 ; Dubey et al, 2023 ; Hans et al, 2022 ; Ibrahim et al, 2022 ; Nimbi et al, 2023 ). It is regarded as a part of regular follow-up by psychologists during this pandemic of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…They frequently worked long hours in an effort to uphold the standard of care. Furthermore, they encountered the formidable obstacle of insufficient accessibility to personal protective equipment (PPE), encompassing masks, gowns, and gloves ( Dubey et al, 2023 ; Ibrahim et al, 2022 ). The limited availability of crucial protective equipment not only increased the likelihood of infection but also induced psychological anguish among nurses, who were concerned about sharing the virus to their families and communities.…”
Section: Introduction and Purposementioning
confidence: 99%
“…26 Treatment primarily focuses on managing symptoms and providing supportive care through the use of antiviral drugs, pain relievers, and fluids to prevent dehydration. [26][27][28] Prevention measures include smallpox vaccination, 29 practicing good hygiene, avoiding contact with infected individuals, isolation and quarantine, and using personal protective equipment. 30,31 Effective contact tracing, early detection, and robust surveillance are also imperative in controlling mpox spread.…”
Section: Introductionmentioning
confidence: 99%
“…Some health workers demonstrated a positive attitude 35,47 displaying a willingness to care for mpox patients and adherence to infection prevention and control measures. 27,37 However, other studies reported negative attitudes, such as fear, stigmatization, [48][49][50] and refusal to care for mpox patients. 51 Satisfactory attitude towards mpox was observed in less than a third (30.7%) of Lebanon healthcare workers.…”
Section: Introductionmentioning
confidence: 99%